2018
DOI: 10.1101/315929
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

T Cell Activation Triggers Reversible Inosine-5'-Monophosphate Dehydrogenase Assembly

Abstract: T cell-mediated adaptive immunity requires naïve, unstimulated T cells to transition from a quiescent metabolic state into a highly proliferative state upon T cell receptor engagement.This complex process depends on transcriptional changes mediated by Ca 2+ -dependent NFAT signaling, mTOR-mediated signaling and increased activity of the guanine nucleotide biosynthetic enzyme inosine-5'-monophosphate (IMP) dehydrogenase (IMPDH). Inhibitors of these pathways serve as potent immunosuppressants. Unexpectedly, we d… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 39 publications
1
6
0
Order By: Relevance
“…We and others previously reported that GTP can stabilize compressed IMPDH2 filaments or drive their disassembly, depending on what other ligands are present (Buey et al 2017; Anthony et al 2017; Duong-Ly et al 2018). To understand how ligand status of the active site tunes the response to GTP, we systematically explored the effects of different ligand combinations on filament assembly.…”
Section: Resultsmentioning
confidence: 89%
See 4 more Smart Citations
“…We and others previously reported that GTP can stabilize compressed IMPDH2 filaments or drive their disassembly, depending on what other ligands are present (Buey et al 2017; Anthony et al 2017; Duong-Ly et al 2018). To understand how ligand status of the active site tunes the response to GTP, we systematically explored the effects of different ligand combinations on filament assembly.…”
Section: Resultsmentioning
confidence: 89%
“…IMPDH activity is upregulated to increase guanine levels in proliferating tissues like tumors and regenerating liver (Tressler et al 1994; Yalowitz & Jayaram 2000; Huang et al 2018; He et al 2018; Nagai et al 1991). IMPDH plays a particularly important role in the immune response, where T-cell activation is dependant on increased production of purine nucleotides, and is associated with IMPDH filament assembly (Gu et al 2000; Zimmermann et al 1998; Duong-Ly et al 2018; Calise et al 2018). As a result, IMPDH is the target of several drugs used in immunosuppressive treatment of both autoimmune disease and organ transplant rejection, and is considered a promising target for antineoplastic agents (Shu & Nair 2008; Liao et al 2017; Bergan et al 2016).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations